Deiksis dalam Rubrik Opini Kaltim Post Agustus 2019 serta Fungsinya sebagai Bahan Ajar Pembelajaran Bahasa Indonesia di SMA - Hidayah, Siti Nur; Ahmad, M. Rusydi; Arifin, Syaiful (Universitas Mulawarman, 2021)
Changes in the context of speech or discourse can often result in errors in the use of deixis in a speech or discourse. This encourages to know the meaning of the speech or discourse. In newspapers, especially opinion rubrics, the proper use of deixis can make the newspaper easier to understand. Opinion is a journalistic product which is writing about the views or opinions of someone from various professions. This study aims to examine the form of deixis in the August 2019 edition of the Kaltim Post opinion rubric and its function as teaching materials for Indonesian language learning in high school. This research is a qualitative research with descriptive method. The source of the data comes from the August 2019 edition of the Kaltim Post daily opinion rubric. The data was obtained using the listening and note-taking technique. The results of this study are 1) found 5 types of deixis namely personal deixis (me, us, you, he, him, them) social deixis (lecturers, pilgrims, Bappenas), place deixis (this and that), time deixis (last week, this year, 2045 later) and discourse deixis (anaphora and cataphora) 2) opinion rubric meets the criteria as teaching materials for editorial text learning in high school.